Respostas
respondido por:
4
Razão da PA
r = a2 - a1
r = -67 - (-73)
r = -67 + 73
r = 6
=====
Encontrar o termo que é o primeiro número positivo
an = a1 + ( n -1) . r
5 = -73 + ( n -1) . 6
5 = -73 + 6n - 6
5 = -79 + 6n
84 = 6n
n = 14
===
Encontra o valor de a14
an = a1 + ( n -1) . r
an = -73 + ( 14 -1) . 6
an = -73 + 78
an = 5
r = a2 - a1
r = -67 - (-73)
r = -67 + 73
r = 6
=====
Encontrar o termo que é o primeiro número positivo
an = a1 + ( n -1) . r
5 = -73 + ( n -1) . 6
5 = -73 + 6n - 6
5 = -79 + 6n
84 = 6n
n = 14
===
Encontra o valor de a14
an = a1 + ( n -1) . r
an = -73 + ( 14 -1) . 6
an = -73 + 78
an = 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás